'Nesting Dragon, Soldier, Spy': Shaping the Narrative on China Through Huawei in UK Parliamentary Debates. - Da Gama, Francisca; Bui, Kim (Journal of Contemporary China, 2025)
This article examines the controversy surrounding 5G in the United Kingdom preceding the decision to remove Huawei from the UK network. We analyse UK parliamentary debates from 2012–2020 against the backdrop of tensions between the United States and China in the race for global leadership in 5G technology. We identify four principal themes in the UK parliamentary discourse: Huawei as innovator and collaborator; a threat to national security; as undermining UK relations with its allies; and embodying opposing values. We argue that the narrative shifts in the UK government's position towards Huawei correspond to Conservative Party internal conflicts on how to navigate the UK's relationship with Huawei in response to geopolitical pressures. We situate this changing narrative within a political sinologism that is used to shape a negative view of Huawei and China.